Iqbāl : Yaurap meṉ - Durrani, S. A. (Lāhaur : Firozsanz, 1999)
On the life and activities of Sir Muhammad Iqbal, 1877-1938, during his stay in Europe; includes facsimile reproductions of his unpublished letters.
Includes bibliographical references and index.
Mode of access: Internet.
In Urdu; some in English.
Keywords: Iqbal, Muhammad, -- Sir, -- 1877-1938.; Iqbal, Muhammad, -- Sir, -- 1877-1938 -- Travel -- Europe; Authors, Urdu -- Biography; Europe -- Description and travel